Analisis Penggunaan Rekam Medik Elektronik Di Rumah Sakit Umum Muhammadiyah Babat - Rizal Rizky Aditya Nugroho; Suratmi; Nurul Hikmatul Qowi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Objective: To analyze the level of Electronic Medical Records (EMR) use by nurses at Muhammadiyah Babat General Hospital and evaluate organizational readiness factors that influence its use.Methods:This study used a descriptive design with a cross-sectional approach and was conducted from June to July 2025. A total of 48 nurses were selected using a cluster random sampling technique. Data collection was conducted using a closed-ended questionnaire developed based on four readiness indicators: human resources (HR), organizational culture, leadership governance, and information technology (IT) infrastructure. Data were analyzed univariately to determine the frequency distribution, percentage, and average value of each variable. Data processing was performed using SPSS version 25.0 for Windows.Results:The majority of nurses (59.2%) were in the moderate category of EMR use, 24.5% were in the low category, and only 14.3% were in the high category. Of the four organizational readiness indicators, IT infrastructure had the highest average score (69.6), while organizational work culture had the lowest score (55.8), indicating persistent barriers to the use of digital technology in the work culture aspect.Conclusion:Although the hospital has adequate infrastructure technically, organizational culture and leadership still need improvement. Recommended efforts include ongoing training, strengthening digital leadership, and establishing a work culture that supports technology integration in clinical services.